2022
DOI: 10.2147/jir.s382069
|View full text |Cite
|
Sign up to set email alerts
|

Pyroptosis and Intervertebral Disc Degeneration: Mechanistic Insights and Therapeutic Implications

Abstract: Low back pain (LBP) is a common problem worldwide, resulting in great patient suffering and great challenges for the social health system. Intervertebral disc (IVD) degeneration (IVDD) is widely acknowledged as one of the key causes of LBP. Accumulating evidence suggests that aberrant pyroptosis of IVD cells is involved in the pathogenesis of IVDD progression, however, the comprehensive roles of pyroptosis in IVDD have not been fully established, leaving attempts to treat IVDD with anti-pyroptosis approaches q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 134 publications
0
13
0
Order By: Relevance
“…Excessive pyroptosis, however, can trigger a severe inflammatory response that results in improper repair of damaged tissues and organs, resulting in a number of inflammatory diseases such as cancer, arthritis, atherosclerosis, sepsis and Parkinson's disease, amongst others. [18][19][20][21][22] In the present study, through a comprehensive review of pyroptosis-related genes (PRGs) in GSE53819 and GSE64634, acquired from the Gene Expression Omnibus (GEO) (https://www. ncbi.nlm.nih.gov/geo) database, we examined the function of PRGs in risk prediction and subtype classification of NPC patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive pyroptosis, however, can trigger a severe inflammatory response that results in improper repair of damaged tissues and organs, resulting in a number of inflammatory diseases such as cancer, arthritis, atherosclerosis, sepsis and Parkinson's disease, amongst others. [18][19][20][21][22] In the present study, through a comprehensive review of pyroptosis-related genes (PRGs) in GSE53819 and GSE64634, acquired from the Gene Expression Omnibus (GEO) (https://www. ncbi.nlm.nih.gov/geo) database, we examined the function of PRGs in risk prediction and subtype classification of NPC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Moderate levels of pyroptosis have been shown to help the body resist pathogen invasion and inflammatory responses mediated by inflammatory factors, which help maintain the stability of the internal environment. Excessive pyroptosis, however, can trigger a severe inflammatory response that results in improper repair of damaged tissues and organs, resulting in a number of inflammatory diseases such as cancer, arthritis, atherosclerosis, sepsis and Parkinson's disease, amongst others 18–22 …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that the over‐production ofreactive oxygen species (ROS), including hydrogen peroxide (H 2 O 2 ), superoxide anion (O 2 •− ), peroxynitrite (ONOO − ), and hydroxyl radical (•OH), significantly disrupts the homeostasis of IVD microenvironment and contributes profoundly to the pyroptosis of NP cells. [ 6–8 ] Particularly, pyroptosis not only provokes the degradation of ECM but also induces secondary inflammation in IVD, thereby complicating the IVD microenvironment and effective interventions. [ 9 ] Hence, we speculated that alleviating the pyroptosis of NP cells by reducing excessive ROS levels can be a promising target for alleviating IVDD.…”
Section: Introductionmentioning
confidence: 99%
“…Ge Y et al. assumed that autophagy regulated inflammasome activation and affected the outcome of cell pyroptosis [ 9 ]. Pyroptosis is a newly discovered form of programmed cell death, which is also involved in NP cells (NPCs) during IDD progression [ 10 ].…”
Section: Introductionmentioning
confidence: 99%